Bioactive Compounds in Coffee as Neuroprotective Agents in Alzheimer's Disease: An in-Silico Study - Himmah, Karimatul; Putri Elok Septiana Dewi (Directorate of Research and Community Services, 2025)
Coffee contains some bioactive compound that has benefits for some health issues. Trigonelline, diterpene cafestol, chlorogenic acid, and caffeine are bioactive compounds found in coffee. We investigate some bioactive compounds in coffee, which could protect from Alzheimer’s disease (AD). Amyloid beta Protein Precursor (APP) plays a role in the accumulation of amyloid toxicity, contributing to the neurodegenerative disorder of AD. This study aims to investigate the potential of four bioactives in coffee that could mitigate the risk of AD by inhibiting APP based on its interaction and binding affinities through an in-silico study. The method includes the prediction of protein use PHYRE2 and small-molecule structures, and visualization with Discovery Studio, molecular docking using Autodock Vina with PyRx 8.0, and analysis of the bioavailability of bioactives using SwissADME. Chlorogenic acid has the highest binding energy compared to other ligands to interact with APP (-6.7 kcal/mol), whereas the other ligands have binding energy scores -4.7 kcal/mol, -6.5 kcal/mol, and -4.5 kcal/mol. However, diterpene cafestol is a promising compound for drug development based on its binding site, bioavailability, high gastrointestinal absorption, drug likeness score of 0.55, and its binding energy score -6,5 kcal/mol, making it a top candidate.